School-Related Factors as Predictors of Learning Outcome among Primary School Pupils in South West, Nigeria (2022)
This study investigated the predictive effects of school related factors on learning outcome among pupils in selected primary schools where Federal Government in collaboration with state governments is carrying out an experimental study in Southwest geopolitical zone, Nigeria. The study adopted a descriptive research design of correlational type. A total number of five hundred (541) and forty-one pupils in Southwest geopolitical zone with ages ranged from 7±1.5 years with mean of 8.41 and 3.75 standard deviation were selected using stratified random sampling technique due to differences in the state of origin and level of monitoring of facilities provided and the research instrument employed was an adapted questionnaire consisting of demographic section, and measures of free tuition, free health care, free feeding, scholarship, availability of teachers, school friendly environment and achievement test on English language and mathematics was attached for learning outcome (using average score in Mathematics and English language tests) of the respondents with 0.76 and 0.73 reliability coefficients respectively. The study answered three research questions using statistical tools like Pearson Product Moment Correlation (PPMC) and Regression analysis. The findings revealed that there was joint contribution of the independent variables to learning outcome of primary school pupils in southwest geopolitical zone of Nigeria; R = 0.648, p<0.05. It further revealed that 40.8% (Adj R2 = 0.408, p<0.05) in the pupils’ learning outcome was due to the prediction of the independent variables. There was significant contribution of all the independent variables. The most potent contributor to learning outcome was school fee and free health care while other variables had inverse contribution. Based on this, researcher conclude that government should strive to provide adequate educational opportunities to the children from inception to enable them have strong educational background and that at the end both the government and parents will reap the fruits of their labour